Model of Back Acupressure, Infant Attachment-Position, and Breast Massage on Breast Milk Factors - Nurul Pujiastuti; Agus Setyo Utomo; Mustayah Mustayah (Health Notions, 2021)
The most common cause of failure in the breastfeeding process is due to various problems experienced by breastfeeding mothers. One of the causes breastfeeding failure is the mother feels that the milk does not come out or only comes out a little. Efforts that can be made to stimulate milk production are combination of complementary therapies, namely back acupressure, baby positioning and attachment, breast massage. The purpose of the study was to analyze the model of mother’s back acupressure, baby position and attachment, breast massage on colostrum and milk production secretion. The research design was descriptive explanatory survey. The sample size was determined based on the rule of the thumb (5 x the number of parameters studied). There were 18 parameters in this study, so the required sample size was 5 x 18 = 90 respondents. The sample was 90 breastfeeding mothers with purposive sampling technique. The sample criteria were mothers who breastfeed babies aged 0-6 months with spontaneous delivery in Sidoarjo Regency. The research was carried out in July-August 2021. Data analysis with structural equation-partial least square (PLS). The results showed that there was an influence of breastfeeding mothers on back acupressure factors, baby position and attachment, breast massage (T=2.587), health care factors on breastfeeding factors (1.957), back acupressure factors, baby position and attachment, breast massage on breastfeeding factors (2,132). Back acupressure, baby positioning and attachment, breast massage can help increase colostrum secretion and breast milk production for breastfeeding mothers. Furthermore, further research can be carried out related to hormonal levels of breastfeeding mothers.Keywords: back acupressure; breast massage; attachment-position